Trichinella spiralis Paramyosin Induces Colonic Regulatory T Cells to Mitigate Inflammatory Bowel Disease - Hao, Chunyue; Wang, Wei; Zhan, Bin; Wang, Zixia; Huang, Jingjing; Sun, Ximeng; Zhu, Xinping (Frontiers in Cell and Developmental Biology, 2021)
Helminth infection modulates host regulatory immune responses to maintain immune homeostasis. Our previous study identified Trichinella spiralis paramyosin (TsPmy) as a major immunomodulatory protein with the ability to induce regulatory T cells (Tregs). However, whether TsPmy regulates gut Tregs and contributes to intestinal immune homeostasis remains unclear. Here we investigate the therapeutic effect of recombinant TsPmy protein (rTsPmy) on experimental colitis in mice, and elucidate the roles and mechanisms of colonic Tregs induced by rTsPmy in ameliorating colitis. Acute colitis was induced by dextran sodium sulfate (DSS) in C57BL/6J mice, and chronic colitis was induced by naïve T cells in Rag1 KO mice. Mice with colitis were pre-treated with rTsPmy intraperitoneally, and clinical manifestations and colonic inflammation were evaluated. Colonic lamina propria (cLP) Tregs phenotypes and functions in DSS-induced colitis were analyzed by flow cytometry. Adoptive transfer of cLP Tregs treated by rTsPmy into Rag1 KO chronic colitis was utilized to verified Tregs suppressive function. rTsPmy ameliorated the disease progress of DSS-induced colitis, reduced pro-inflammatory responses but enhances regulatory cytokines production in DSS-induced colitis. Moreover, rTsPmy specifically stimulated the expansion of thymic-derived Tregs rather than the peripherally derived Tregs in the inflamed colon, enhanced the differentiation of effector Tregs (eTregs) with higher suppressive function and stability in colitis. This study describes the mechanisms of colonic Tregs induced by the Trichinella-derived protein rTsPmy in maintaining gut immune homeostasis during inflammation. These findings provide further insight into the immunological mechanisms involved in the therapeutic effect of helminth-derived proteins in inflammatory bowel diseases.